2022
DOI: 10.3389/fpsyg.2022.971654
|View full text |Cite
|
Sign up to set email alerts
|

Strategic orientation, business model innovation and corporate performance—Evidence from construction industry

Abstract: In the highly competitive Chinese construction market, developing a strategic orientation alone fails to maintain the sustainable competitive advantage of firms. In this paper, the mechanism of strategic orientation and business model innovation on corporate performance in a dynamic environment is investigated. Based on a sample of 356 Chinese construction firms, the partial least squares structural equation modelling (PLS-SEM) was adopted to test the hypotheses. It is found that entrepreneurial orientation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 145 publications
0
4
0
Order By: Relevance
“…We concluded that R&D effort is conductive to business model innovation, thereby extending the research on the antecedents of business model innovation. The antecedents of business model innovation have been explored in many aspects, such as organizational search [ 82 ], big data analytics capabilities [ 83 ] and strategic orientation [ 84 ]; however, few researchers have paid attention to the role of firms’ R&D effort. Similarly, our results also enrich the research on the outcomes of R&D effort.…”
Section: Discussionmentioning
confidence: 99%
“…We concluded that R&D effort is conductive to business model innovation, thereby extending the research on the antecedents of business model innovation. The antecedents of business model innovation have been explored in many aspects, such as organizational search [ 82 ], big data analytics capabilities [ 83 ] and strategic orientation [ 84 ]; however, few researchers have paid attention to the role of firms’ R&D effort. Similarly, our results also enrich the research on the outcomes of R&D effort.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis underscores the interdependence of innovation and R&D, emphasizing the importance of nurturing these connections [139]. Public investment in R&D acts as the foundation for a nation's innovation prowess, but policy frameworks, human capital, and market access also play pivotal roles [140,141]. This holistic approach paves the way for an innovative future where ideas flourish, powered by knowledge, enterprise, and collective determination.…”
Section: Technology/science and Digital Society Factormentioning
confidence: 93%
“…A growing number of publications have attempted to understand the role of business models in fulfilling organisational objectives [99][100][101]. As mentioned earlier, Brady, Davies [73] was among the first to present the 'Built Environment Solution Provision (BESP)', a concept of bundling construction products and services into an integrated value chain, enhancing repeatability and standardisation.…”
Section: Generic Business Model Researchmentioning
confidence: 99%